Hydrogen trapping and fatigue crack growth property of low-carbon steel in hydrogen-gas environment. (September 2017) - Yamabe, Junichiro; Yoshikawa, Michio; Matsunaga, Hisao; Matsuoka, Saburo
Highlights: FCG tests were performed with low-carbon steel. The hydrogen-trapping sites and diffusivity were determined. Depending on the test conditions, the FCG was accelerated. A novel parameter representing the local hydrogen at the crack tip was introduced. The novel parameter quantified the FCG acceleration under various test conditions. Abstract: Fatigue crack growth (FCG) tests for compact-tension specimens of low-carbon steel were performed under various combinations of hydrogen pressures (0.1–90 MPa), test frequencies (0.001–10 Hz), and test temperatures (room temperature, 363 K, and 423 K). For quantifying the FCG acceleration, the hydrogen trapping and diffusivity of prestrained specimens were determined. Depending on the test conditions, the FCG was accelerated. The hydrogen-assisted FCG acceleration always accompanied localized plastic deformations near the crack tip. The onset of the FCG acceleration was roughly quantified by using a simplified parameter representing the gradient of the hydrogen concentration at the crack tip.